2022
DOI: 10.1002/pro.4327
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach reveals how lipo‐chitooligosaccharides interact with the lysin motif receptor‐like kinase MtLYR3

Abstract: N-acetylglucosamine containing compounds acting as pathogenic or symbiotic signals are perceived by plant-specific Lysin Motif Receptor-Like Kinases (LysM-RLKs). The molecular mechanisms of this perception are not fully understood, notably those of lipo-chitooligosaccharides (LCOs) produced during root endosymbioses with nitrogen-fixing bacteria or arbuscular mycorrhizal fungi. In Medicago truncatula, we previously identified the LysM-RLK LYR3 (MtLYR3) as a specific LCO-binding protein. We also showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This hypothesis is supported by the AM phenotype of Mtlyk9 mutants (LYK-I subclass; Gibelin-Viala et al 2019), which is enhanced in a Mtlyk9/Mtnfp double mutant (Feng et al 2019). Other contenders for a role in AM in M. truncatula are MtLYR3 (LYR-IIIA subclass) since loss of LCO binding in MtLYR3 orthologs can be associated with loss of AM (Bouchiba et al 2022;Malkov et al 2016) and MtLYR8 (LYR-IB subclass) since, like LYR-IA, this subclass is absent in the non-AM species A. thaliana (Buendia et al 2018) and shown to be involved in AM in barley (Li et al 2022). Clearly, analysis of double, triple and higher order mutants are required to unravel possible LysM-RLK redundancy in AM.…”
Section: Duplication and Divergence Of Lyr-ia In M Truncatulamentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is supported by the AM phenotype of Mtlyk9 mutants (LYK-I subclass; Gibelin-Viala et al 2019), which is enhanced in a Mtlyk9/Mtnfp double mutant (Feng et al 2019). Other contenders for a role in AM in M. truncatula are MtLYR3 (LYR-IIIA subclass) since loss of LCO binding in MtLYR3 orthologs can be associated with loss of AM (Bouchiba et al 2022;Malkov et al 2016) and MtLYR8 (LYR-IB subclass) since, like LYR-IA, this subclass is absent in the non-AM species A. thaliana (Buendia et al 2018) and shown to be involved in AM in barley (Li et al 2022). Clearly, analysis of double, triple and higher order mutants are required to unravel possible LysM-RLK redundancy in AM.…”
Section: Duplication and Divergence Of Lyr-ia In M Truncatulamentioning
confidence: 97%
“…We identified a high affinity (nM range) LCO binding protein in the PM fraction of cell cultures as the LYR-IIIA protein, MtLYR3 (Fliegmann et al 2013;Gressent et al 1999). MtLYR3 is located next to and in inverse orientation to MtNFP (Buendia et al 2018;Gough et al 2018), and legume orthologs of MtLYR3 bind LCOs (Bouchiba et al 2022;Malkov et al 2016). We also used a radiolabelled LCO-V ligand (LCO-V(C18:1,NMe, 35 S)), which has more similarity to a Myc-LCO than the S. meliloti NFs, to characterise LCO binding to the tomato and P. hybrida LYR-IA protein, and showed the relevance of these proteins for AM (Girardin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…), and Parasponia andersonii ( P. andersonii ). 17 , 18 , 19 , 20 , 21 , 22 , 23 Besides CO, AMF also produce LCO, 8 and several LysM-RLKs have been shown to bind LCO in legumes 24 , 25 , 26 , 27 , 28 , 29 , 30 and act as pivotal components for LCO detection in the root nodule symbiosis (RNS), notably MtNFP / LjNFR5 and MtLYK3 / LjNFR1 in legumes M. truncatula and Lotus japonicus . 31 , 32 , 33 , 34 , 35 , 36 , 37 These LCO receptors, which are essential for the RNS, also contribute to the AMS, as evidenced by a quantitative reduction in AMF colonization in the cerk1 / nfp double mutant, as compared with cerk1 alone.…”
Section: Introductionmentioning
confidence: 99%
“…Several LysM-RLK/Ps have been described as high affinity LCO or long-chain CO binding proteins [8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%